Облік надурочних годин для працівників, які працюють у критичній інфраструктурі під час війни - Гуріна, Наталія Валеріївна; Купріянова, Анастасія Олександрівна (Видавничий дім «Гельветика», 2024)
У статті досліджується питання обліку надурочних годин для працівників критичної інфраструктури під час війни. Особлива увага приділяється специфіці організації обліку в умовах підвищеного навантаження на підприємства та необхідності підтримання безперервної роботи життєво важливих об’єктів. Аналізуються чинні норми трудового законодавства та їхня адаптація до надзвичайних умов воєнного стану. У статті також розглядаються методи організації справедливого та точного обліку надурочних годин, а також механізми компенсації працівникам за додаткові робочі навантаження. Результати дослідження можуть бути корисними для покращення організації праці в кризових умовах і забезпечення захисту прав працівників. Правильний підхід ¬до обліку допомагає оптимізувати розподіл ресурсів і поліпшити координацію роботи персоналу.

The article examines the issue of accounting for overtime hours for critical infrastructure employees during wartime, taking into account the specifics of their work under conditions of increased workload on enterprises and the need to maintain the continuous operation of vital facilities. Critical infrastructure facilities include energy, water supply, transport and other important enterprises that must operate even in a state of emergency, including during hostilities. Particular attention is paid to the requirements of labour legislation governing overtime and their adaptation to modern conditions. In a time of war, when companies are operating under increased pressure, it is important not only to record the number of overtime hours but also to ensure that this recording complies with applicable laws and regulations and that correct payments are made to employees. According to standard regulations, overtime should not exceed 120 hours per year for one employee. However, during martial law, temporary changes or relaxation of this requirement may be introduced. The study analyses not only the current legal provisions, but also suggests ways to improve accounting to meet the realities of wartime. It emphasises the importance of providing employees with fair compensation for overtime, including both monetary payments and additional days of rest. The use of a comprehensive system of compensation and benefits can help to reduce stress among employees, improve their physical and mental health, and increase overall productivity in wartime. The article also discusses methods of organising transparent and accurate time tracking using modern digital tools that minimise the potential for errors or abuse. In addition, the article contains recommendations on how to avoid employee burnout due to excessive workloads. An important aspect of the study is the proposals for flexibility in personnel management, including the possibility of temporary redistribution of work tasks among employees. The results of the study may be useful for critical infrastructure enterprises in order to improve labour organisation in times of crisis, optimise the use of resources, increase the level of coordination and ensure the protection of employees' rights.
Keywords: критична інфраструктура; надурочні години; принцип оплати; облік робочого часу; ефективність праці; critical infrastructure; overtime; payment principle; working time accounting; labour efficiency